Heavy Metal Pollution and Ecological Risk Assessment of the Agriculture Soil in Xunyang Mining Area, Shaanxi Province, Northwestern China - Zhu, Daiwen; Wei, Yang; Zhao, Yonghua; Wang, Qilong; Han, Jichang (Bulletin of environmental contamination and toxicology, 2018)
Mining is considered to be one of the most significant sources of environmental pollution with regard to heavy metals. Mineral mining causes large quantities of mercury, cadmium, and other elements to be released into the environment and naturally poses a serious threat to environment. This paper will analyze the pollution status of agricultural soil caused by the mining of heavy metals in various mining areas in the Xunyang County in the Shaanxi Province of China, an area in famous for its resource mining. Equally, it will look at the potential ecological risk assessment process that is used to analyze the ecological risks of mining heavy metals in agricultural soil located in the surrounding areas. Based on the soil investigation, As pose a moderate ecological risk on the Au mining area. In addition, the Hg metals pose a significantly high potential ecological risk and Cd metals pose a considerable potential ecological risk on the Hg mining area. In the Pb–Zn mining area, a significantly high potential ecological risk was mainly posed by Cd. These results suggest that many heavy metals pose a high potential ecological risk on the agricultural soil in these three mining areas in the Xunyang County, and may cause elevated heavy metal contents in crops, eventually jeopardizing the health of local residents who consume food grown in polluted soil.